PENGARUH MOTIVASI DUA-FAKTOR HERZBERG TERHADAP PELAKSANAAN DOKUMENTASI PROSES KEPERAWATAN DI INSTALASIRAWAT INAP RSUD PURBALINGGA - -, hartati; -, handoyo (LPPM STIKES MUHAMMADIYAH GOMBONG, 2011)
Based on Herzbergâ€™s two-factor motivation theory, there are intrinsic and extrinsic factors influencing work performance. Nursing document is an authentic document, eligible for evaluation and serves as a legal aspect to assess nursing quality provided by hospitals to their patients. This study aim is to analyze the influence of intrinsic motivation factors (the work itself, opportunity to progress, appreciation of others, and responsibility) and extrinsic motivation factors (compensation, work condition, supervision, and interpersonal relationship) on nursing documentation. This study used cross sectional survey. The sample consists of 125 nurses selected by simple random sampling. Data were collected using questionnaire. Multiple regression method was used to analyze the data.This study shows that none of the intrinsic motivation factors significantly influences the dependent variable, while all of the extrinsic motivation factors significantly influence it.Â The coefficient of determination is very high, 0.917 meaning that the model predict 91.7 percent of the cases correctly. Extrinsic motivation factors significantly influence nursing documentation at RSUD Purbalingga. Those factors, therefore, should be closely taken care in order to improve nursing documentation at the hospital. Keywords: Herzbergâ€™s two-factor motivation theory, Nursing documentation